Analisis Tingkat Pemahamahan Label Gizi Dan Pengaruhya Terhadap Keputusan Pembelian Produk Makanan Kemasan - Kezia Natalia Sagala; Sri Wahyuningsih; Endah Subekti; Rossi Prabowo (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Nutrition information labels are one of the sources of information that consumers can use in selecting packaged food products. This study aimed to analyze the levels of knowledge, understanding, and consideration of nutrition information labels, as well as their influence on the purchasing decisions of packaged food products among Agribusiness students at the Faculty of Agriculture, Wahid Hasyim University Semarang. The study used a survey method involving 63 respondents. Data were analyzed using descriptive analysis and multiple linear regression analysis. The results showed that the knowledge variable obtained a percentage of 82% (strongly agree), the understanding variable 76% (strongly agree), and the consideration variable 75% (agree). Simultaneously and partially, the three variables did not have a significant effect on purchasing decisions (sig. 0.254 > 0.05; partial sig. values of 0.703, 0.138, and 0.205). The coefficient of determination (R²) of 0.066 indicated that the three variables explained only 6.6% of purchasing decisions, while the remaining was influenced by other factors.